Imported Crimean-Congo hemorrhagic fever cases in Istanbul - GARGILI KELEŞ, AYŞEN (BIOMED CENTRAL LTD, 2007)
We described a series of imported cases of Crimean-Congo Hemorrhagic Fever (CCHF) in Istanbul and investigated the genetic diversity of the virus. All the suspected cases of CCHF, who were applied to the health centers in Istanbul, were screened for CCHF virus (CCHFv) infection by using semi-nested Polymerase Chain Reaction (PCR) following RT-PCR. Simultaneous blood samples were also sent to the national reference laboratory in Ankara for serologic investigation. In 10 out of 91 patients, CCHFv was detected by PCR, and among 9 out of 10, anti-CCHFv IgM antibodies were also positive. Clinical features were characterized by fever, myalgia, and hemorrhage. The levels of liver enzymes, creatinine phosphokinase, and lactate dehydrogenase were elevated, and bleeding markers were prolonged. All the cases were treated with ribavirin. There was no fatal case. All the strains clustered within the same group as other Europe/Turkey isolates.
Keywords: CLINICAL-FEATURES; GENETIC-ANALYSIS; VIRUS; OUTBREAK; TURKEY; INFECTION